Anticipatory discourse in prenatal education - Hanell, Linnea (Discourse & Communication, 2018)
This article explores communicative aspects of preparing others, by studying prenatal education classes in which midwives prepare expectant parents for delivery. Data include documentation from classes and interviews with the presenters. This twofold dataset enables investigation into how ideologies of communication figure into the production of discourse. A dominant idea is that discourse can stand in for lived experience in the endeavor to decrease nervousness and fear in the expectant parents. The observation data are therefore analyzed by paying attention to how the expectant parents’ future deliveries are discursively represented. Drawing on the conceptual framework for analyzing anticipatory discourse, the study shows how the midwives largely frame this future as predictable and the mother as highly agentive. When addressing unexpected turbulence, however, the midwives use the opportunity to stress the agency of medical professionals to maintain a representation of the delivery event as generally predictable.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzUwNDgxMzE3NzM1NzA4